Computational Thinking Educationfor Students of aPost-Graduate Degree in the Humanities: Flipped Classroom Experiences - Pareja Lora, Antonio (2020)
This paper presents the results of two different experiences about computational thinking acquisition,gained within a formal subject taught in a multidisciplinary (Digital Humanities) master program of a face-to-face teaching university of Spain, following a blended learning approach and using flipped classroom techniques. These results have been obtainedafter imparting lecturing this subject for two consecutive academic years,with similar but distinctive methodologies each. In effect, even though both of them can be considered task-based(or, alternatively, learning-by-doing-based), the first one has focused on grouplearningandhas been inspired by the computer engineering technique of evolutionary prototyping; whereasthe second one builds upon individual learning and case-based (or example-based) learning. Thus, the paper details the parameters defined for each experience and methodology (that is, the participants, the materials, the procedures and the evaluation criteria), together with the main conclusions drawn from this study like, for instance, that group learning has not helped as much as individual learning (at least in this case)identify and correct the errors that occurred while assimilating the contents of the subject.